To Flip or Not to Flip: What Are the Questions? - Shawn R. Simonson (MDPI AG, 2017)
The flipped classroom has been receiving a lot of press lately as a more desirable way to manage the classroom and help students learn. However, flipping the classroom may not be appropriate for every course or every instructor. There may be a time when other active learning strategies are more appropriate to meet learning outcomes, student needs, and instructor capacity. This manuscript will discuss what flipping is and the decisions that an instructor might consider before flipping their classroom which might also enhance their implementation of this and other teaching strategies. A decision matrix is provided to illustrate this process.